Letak Keberadaan Kuta Bara: Narasi dan Dekonstruksi - Adi Alamsyah (Heritage of Nusantara: International Journal of Religious Literature and Heritage, 2025)
This article examines Kuta Bara, one of the vassal kingdoms of Majapahit, with a particular focus on its localization and historical significance during the reign of Hayam Wuruk. The nature of Kuta Bara remains a subject of debate among local historians in Jember, East Java, particularly concerning its location and function. Based on written sources, some scholars have identified Kuta Bara as a Buddhist religious site situated in Cakru village. However, recent archaeological discoveries have prompted a reassessment of these interpretations, necessitating a more comprehensive historical analysis. Employing established historical research methods e.g., heuristics, verification, interpretation, and historiography, this study reevaluates existing perspectives on Kuta Bara. It proposes that rather than a religious site, Kuta Bara functioned as a trading city located in the vicinity of Kraton village. By integrating both textual sources and material evidence, this article offers a revised interpretation of Kuta Bara’s role within the broader political and economic networks of Majapahit.